Implementasi Promosi Digital Di Giggle Box Cafe And Resto Kota Mataram Untuk Mengedukasi Konsumen - Febriana, Widia; Palit, Juliana; Ardiansyah, Lalu Yayan (Income : Digital Business Journal, 2023)
Giggle box cafe and resto is a hangout place that does marketing with education. Education-based promotion is widely practiced to overcome the boredom of advertising. The advantage of education-based marketing is that audiences will not only see it as a marketing effort but will directly feel the real value of being a smarter buyer. The purpose of this research is to find out how the implementation of digital promotions in giggle box cafes and restaurants educates consumers. This research is a qualitative research using descriptive qualitative research methods. The location of this research is the address at giggle box cafe and restaurant jalan. Pejanggik, cilinaya, cakranegara district, mataram city, west nusa tenggara. The steps of data collection were taken through the process of interviewing, documenting and observing while the data analysis step was taken by collecting data from the interview process to a number of related parties, in this case the owner of the giggle box cafe and restaurant, then reducing the results of the interviews, then presenting the data in the form of a presentation. Data and research analysis. From the results of this study it can be seen that education-based marketing as a promotion strategy is quite good, they adapt their educational content to the characteristics of the social media they use. Even so, one drawback is related to the digital promotional activities that they carry out, because giggle box cafe and restaurant does not apply an evaluation stage.